OBSERVATIONS ON THE LIFE HISTORY AND FEEDING HABITS OF THE INDIAN SARDINE, SARDINELLA LONGICEPS (CUV. & VAL.) - M. D. K KUTHALINGAM M,M. Se., PH. D (Research Center for Biology, 1960)
abstract not available